Analisis Transformasi Model Pendidikan Kewarganegaraan Berbasis SDGs di Sekolah Menengah Atas Bandar Lampung - Ade Aransyah; Risma Margaretha Sinaga; Agus Suyatna; Sunyono Sunyono; Hasan Hariri (University of Muhammadiyah Malang, 2026)
The implementation of Sustainable Development Goals (SDGs)-based education in civics education at the secondary school level reveals a gap between policy and classroom practice, particularly regarding the contextual integration of sustainability values and the values of Pancasila. This study aims to analyze the implementation of SDG-based education in secondary schools in Bandar Lampung City and to develop an operational learning model. The approach used is qualitative with an exploratory case study design. Data were collected through interviews with the principal, teachers, and students at SMA IT Baitul Jannah, participatory observation, and document analysis, and were then analyzed using thematic analysis techniques. Research findings indicate that the integration of the SDGs into teaching remains implicit and has not yet been systematically incorporated into the curriculum or pedagogical strategies. Teachers have linked course content to social and environmental issues, but have not explicitly utilized the SDG framework. The internalization of Pancasila values has taken place, though it remains predominantly normative and has not yet been reflectively connected to global issues. Limited teacher understanding, a lack of training, suboptimal use of technology, and weak collaboration are the main obstacles. On the other hand, students have shown enthusiasm for project-based learning and real-world issues. This study resulted in the Civic-SDG Transformative Learning Model (CSTLM), which integrates an SDG-based curriculum, transformative pedagogy grounded in critical pedagogy and deep thinking skills, digital technology, and the values of Pancasila. This model is implemented through the stages of issue identification, SDG analysis, value reflection, action, and evaluation. These findings provide conceptual and practical contributions to the development of sustainability-based civic education in Indonesia.